2020
DOI: 10.1037/vio0000289
|View full text |Cite
|
Sign up to set email alerts
|

Is dating aggression victimization a risk factor or a consequence of other forms of victimization? A longitudinal assessment with Latino youth.

Abstract: Objective: The aim of this analysis was to evaluate whether dating violence is a risk factor for other forms of victimization, or if other forms of victimization, including polyvictimization, are a risk factor for dating violence. Method: This study used data from both waves of the Dating Violence Among Latino Adolescents study, which surveyed 574 Latino youth using the random-digit-dial methodology, and queried participants about past-year dating violence victimization, other forms of victimization, help-seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Through a path model of longitudinal data from the Raising Healthy Children (RHC) project, one study detected that child maltreatment before 13 years of age was a significant predictor of later physical teen dating violence victimization in both girls and boys (Maas et al, 2010 ). Using data from both waves of the Dating Violence Among Latino Adolescents study, child maltreatment, conventional crime, and polyvictimization (measured at between 12 and 18 years of age) were found to be predictive of dating violence victimization one year later (Cuevas et al, 2020 ). Similarly, a close relation between peer victimization and dating violence victimization was confirmed in a longitudinal study (Brooks-Russell et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through a path model of longitudinal data from the Raising Healthy Children (RHC) project, one study detected that child maltreatment before 13 years of age was a significant predictor of later physical teen dating violence victimization in both girls and boys (Maas et al, 2010 ). Using data from both waves of the Dating Violence Among Latino Adolescents study, child maltreatment, conventional crime, and polyvictimization (measured at between 12 and 18 years of age) were found to be predictive of dating violence victimization one year later (Cuevas et al, 2020 ). Similarly, a close relation between peer victimization and dating violence victimization was confirmed in a longitudinal study (Brooks-Russell et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This inverse association in girls could be explained by the effect of learned helplessness, psychoemotional disorders linked to the violence suffered, or discipline associated with gender patterns (González-Ortega et al, 2008). Cuevas et al (2020) also suggested that exposure to aversive or violent events can, in some instances, trigger a greater perception of vulnerability, stimulate protection and risk avoidance mechanisms, and decrease interactions with the threatening stimuli, reducing the risk of perpetrating other forms of violence. The results of this study suggest that not all social groups experience, elaborate, and react in the same way to the violence suffered.…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of victimization in Wave 1 (27%) and Wave 2 (19.7%) was peer/sibling victimization. Other papers have addressed victimization rates (Cuevas et al, 2014(Cuevas et al, , 2020Mariscal et al, 2021;Sabina et al, 2016). Not assessed again at follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Another national study that was specifically developed for Latinos, employed a broad definition of violence, and was longitudinal—the Dating Violence among Latino Adolescents (DAVILA) study—found 53% of Latino youth were victimized at the first wave—37% peer and sibling victimization, 19.5% dating victimization, 18% conventional crime, 18% child maltreatment, and 5% stalking (Cuevas et al, 2014). Wave 2 data highlighted how victimization at Wave 1 was associated with elevated risk of victimization at Wave 2 (Cuevas et al, 2020; Sabina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%